Virilizing adrenal carcinoma in a 3-year-old boy: A rarity - Kumar, Suresh; Tiwari, Punit; Das, Ranjeet; Kundu, Anup Kr (Indian Journal of Medical and Paediatric Oncology, 2010)
A 3-year-old boy presented with iso-sexual precocious puberty for 18 months. Radiological images revealed left suprarenal mass and hormonal profile showed markedly increased testosterone and dehydroepiandrosterone-sulfate. The child underwent open adrenalectomy and histopathology revealed adrenocortical carcinoma. At 3 months follow-up, the child is doing well.
Keywords: Adrenal carcinoma; adrenalectomy; virilization